Erratum to: The use of thermal hydrogen decrepitation to recycle Nd-Fe-B magnets from electronic waste - Editorial (Journal of Mining and Metallurgy. Section B: Metallurgy)
This erratum concerns a correction in the affiliation of the original article [1] on page 415 and 424. Link to the corrected article 10.2298/JMMB200207032P